2022
DOI: 10.1007/s11356-021-17998-y
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing asymmetric effects of cryptocurrency demand on environmental sustainability

Abstract: When bitcoin (BTC), the first pioneering cryptocurrency was released in 2009, it was considered an apolitical currency. Besides, the possible effect of BTC and other cryptocurrencies on either financial markets or transactions has been widely discussed. However, the environmental effects of cryptocurrency demand have been ignored. Here, this study examines the nexus between cryptocurrencies and environmental degradation by employing standard and asymmetric causality methods. The Toda-Yamamoto and bootstrap-aug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The study done by Erdogan et al (2022) provides the evidence where causal association between crypto development and environmental degradation was found. The study applied Toda Yamamoto test to evaluate the association between constructs.…”
Section: Cryptocurrency and Environmental Degradationmentioning
confidence: 97%
“…The study done by Erdogan et al (2022) provides the evidence where causal association between crypto development and environmental degradation was found. The study applied Toda Yamamoto test to evaluate the association between constructs.…”
Section: Cryptocurrency and Environmental Degradationmentioning
confidence: 97%
“…Since cryptocurrencies are energy intensive, there are natural environmental effects. This important issue has been investigated by Erdogan et al (2022) using asymmetric causality tests developed by Hatemi-J (2012). It is found that there are negative asymmetrical environmental causal impacts of the demand for major cryptocurrencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since cryptocurrencies are energy intensive, there are natural environmental effects. This important issue has been investigated by Erdogan et al. (2022) using asymmetric causality tests developed by Hatemi-J (2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, it is necessary to find new approaches to mining that are more environmentally friendly, taking into account the mining process and the conditions that encourage individuals and legal entities to engage in this activity. The relationship between the mining process, the increase in the network hashrate and the amount of electricity consumed was established (Erdogan et al, 2022). The potential bidirectional relationship between the price of cryptocurrency and electricity consumption remains unknown.…”
Section: Literature Reviewmentioning
confidence: 99%